Public perception on safety awareness of petrol station / Muhammad Firdaus Zakaria - Zakaria, Muhammad Firdaus (Faculty of Architecture, Planning and Surveying, 2013)
In Malaysia until October 2010 the total number of petrol stations is 3182 units and 332 units are mini petrol stations.The term ‘petrol station’ used in Malaysia, which in other countries also known as petrol filling station, fueling station, garage, gasbar, gas station, petrol pump, petrol garage, petrol kiosk, service station, or servo, is a facility which sells fuel and usually lubricants for motor vehicles. The petrol filling station consists of a petrol bar with petrol outlets and typically with other associated facilities such as car washes, automotive services, convenience stores and food services. Service stations are open for long hours, keep cash on the premises and have minimal staffing at night, all of which may be contributing factors for robbery. Based on a researched its is stated that a petrol filling station ‘PFS is a hazardous facility and it needs special care in design, construction, installation and maintenance of its components so that they remain safe and secure throughout the life span of the station and do not cause explosion or other untoward incident. PFS are particularly hazardous workplaces. Hazard can be a situation, condition or environment which has a potential to cause harm, damage, human injury or ill health or combination of these.This study seeks the public perception on safety awareness of petrol station. The study involved a total of 100 respondents and among them are mostly users including OKUs, the staffs and several owners of the petrol stations. The result showed that the majority of the respondents visit petrol stations 4 times in week. Most of them used to go to the petrol station for refueling petrol, diesel, NGV or other petroleum products services. Majority of respondents agreed that the kiosk should be operating in 24 hours to ease public to use the facilities provided at petrol station and commented that the place to be added more safety features such as security guard and cctv in order to avoid robbery and snatching.The study also showed other results such as the level of knowledge of respondents about awareness of fire and explosion, accident and injury, and robbery, extortion